PENERAPAN METODE DMAIC DALAM MENURUNKAN DEFECT CANVAS PADA MESIN TOPING CALLENDER DI PT XYZ (Jurnal Inovisi (Teknik Industri), 2017)
AbstractPT. XYZ is the largest integrated tire manufacturer in Southeast Asia, producing and distributing high quality tires for motorcycles. In this case PT. XYZ wants to reduce production costs by reducing the defect treatment that occurs in the Topping Calender machine. The average Defect Section of the Topping Calendar from March to August is 22,988 kg. By applying the DMAIC concept. At the define stage, it is known that the biggest contributor to defect treatment is folding treatment by 60% of the total defect treatment. The measure stage found a DPMO value of 8,580 with a sigma value of 3.89. The Analyze stage using the fishbone diagram shows that the cause of the folding treatment is due to the liner which has folding characteristics at the edge of the liner and because the wind up speed motor wind up process cannot keep up with the feeding speed when the accumulator rises. The improve step is to reduce the defect treatment by replacing the liner with the non-folding characteristic of the liner edges and using an automatic pressure regulator based on the treatment length. The control stage by calculating the DPMO value after the improve stage obtained a DPMO value of 5,500 with a sigma value of 4.05 and adding a pressure brake column and appearance liner to the production job set up. The results of applying the improvement can reduce the DPMO value and increase the sigma level value on the defect treatment. Can save costs of Rp. 205,524,864. Keywords: defect, DMAIC, canvas AbstrakPT. XYZ adalah produsen ban terpadu terbesar di Asia Tenggara, memproduksi dan mendistribusikan ban berkualitas tinggi untuk sepeda motor. Dalam hal ini PT. XYZ  ingin menurunkan biaya produksi denga nmenurunkan defect treatment yang terjadi pada mesin Topping Calender. Defect Section Topping Calender rata-rata bulan maret sampai agustus yaitu 22.988 kg. Dengan menerapkan konsep DMAIC. Pada tahap define diketahui penyumbang terbesar defect treatment yaitu treatment melipat sebesar 60% dari total semua defect treatment. Tahap measure didapat inilai DPMO 8.580 dengannilai sigma 3,89. Tahap analyze dengan menggunakan diagram tulang ikan diketahui penyebab treatment melipat yaitu karena  liner yang mempunyai karakteristik melipat pada pinggir liner dan karena disebabkan pada proses wind up speed motor wind up tidak bisa mengimbangi speed feeding saat accumulator naik. Tahap improve untuk mengurangi defect treatment melipat dengan mengganti liner dengan karakteristik tidak melipat pada bagian pinggir liner dan menggunakan pressure regulator otomatis berdasarkan panjang treatment. Tahap control dengan menghitung nilai DPMO setelah tahap improve didapatkan nilai DPMO sebesar 5.500 dengan nilai sigma 4,05 dan menambahkan kolom pressure brake dan appearance liner pada job set up produksi. Hasil penerapan perbaikan dapat menurunkan nilai DPMO dan meningkatkan nilai level sigma pada defect treatment. Dapat menghemat biaya sebesar Rp. 205.524.864. Kata kunci: defect, DMAIC, canvas